(untitled) - Priest, Joseph (New York, 1991)
The fourth edition of Joseph Priest's Energy draws heavily on the experience of instructors who used earlier editions. It is designed for environmental science courses for non-science majors and is suitable for fulfilling their science requirement.
Keywords: Nguồn điện,Power resources